Modeling and Manufacturing of a Micromachined Magnetic Sensor Using the CMOS Process without Any Post-Process - Tseng, Jian-Zhi (MDPI, 2014)
The modeling and fabrication of a magnetic microsensor based on a magneto-transistor were presented. The magnetic sensor is fabricated by the commercial 0.18 μm complementary metal oxide semiconductor (CMOS) process without any post-process. The finite element method (FEM) software Sentaurus TCAD is utilized to analyze the electrical properties and carriers motion path of the magneto-transistor. A readout circuit is used to amplify the voltage difference of the bases into the output voltage. Experiments show that the sensitivity of the magnetic sensor is 354 mV/T at the supply current of 4 mA.